A New Search Algorithm for Reducing the Incidence of Missing Cottonoids in the Operating Theater - Abhinandan Reddy; Rajat Mahajan; Tarush Rustagi; Shakti A. Goel; Murari L. Bansal; Harvinder Singh Chhabra (Asian Spine Journal, 2019)
Study Design Retrospective study. Purpose Missing cottonoids during and after spinal surgery is a persistent problem and account for the most commonly retained surgical instruments (RSIs) noticed during a final cottonoid count. The aim of this study was to enumerate risk factors and describe the sequence to look out for misplaced cottonoids during spinal surgery and provide an algorithm for resolving the problem. Overview of Literature There are only a few case reports on RSIs among various surgical branches. The data is inconclusive and there is little evidence in the literature that relates to spinal surgery. Methods This retrospective study was conducted at Indian Spinal Injuries Centre. The data was collected from hospital records ranging from January 2013 to December 2017. The surgical cases in which cottonoid counts were inconsistent during or after the procedure were included in the study. The case files along with operating theater records were thoroughly screened for selecting those in which there was confirmed evidence of such an event. Results There were 7,059 spinal surgeries performed during the study period. Fifteen cases of miscounts were recorded with an incidence of one in every 471 cases. Cottonoids were most commonly lost under the shoes of the surgeon or assistants. In two instances, cottonoids were found in the surgical field and trapped in the interbody cage site. Based on these locations, a systematic search algorithm was created Conclusions This study enumerates RSI risk factors in spinal surgical procedures and describes steps that can be followed to account for any missing cottonoids. The incidence of missing cottonoids can be decreased using a goal-oriented approach and ensuring that surgical teams work in collaboration.